The LEGA-C and SAMI galaxy surveys: quiescent stellar populations and the mass–size plane across 6 Gyr. Issue 3 (16th March 2022) - Barone, Tania M; D'Eugenio, Francesco; Scott, Nicholas; Colless, Matthew; Vaughan, Sam P; van der Wel, Arjen; Fraser-McKelvie, Amelia; de Graaff, Anna; van de Sande, Jesse; Wu(吳柏鋒), Po-Feng; Bezanson, Rachel; Brough, Sarah; et al.
ABSTRACT: We investigate changes in stellar population age and metallicity ([Z/H]) scaling relations for quiescent galaxies from intermediate redshift (0.60 ≤ z ≤ 0.76) using the LEGA-C Survey to low redshift (0.014 ≤ z ≤ 0.10) using the SAMI Galaxy Survey. Specifically, we study how the spatially integrated global age and metallicity of individual quiescent galaxies vary in the mass–size plane, using the stellar mass M * and a dynamical mass proxy derived from the virial theorem M D ∝ σ 2 R e . We find that, similarly to at low redshift, the metallicity of quiescent galaxies at 0.60 ≤ z ≤ 0.76 closely correlates with M / R e (a proxy for the gravitational potential or escape velocity), in that galaxies with deeper potential wells are more metal-rich. This supports the hypothesis that the relation arises due to the gravitational potential regulating the retention of metals by determining the escape velocity for metal-rich stellar and supernova ejecta to escape the system and avoid being recycled into later stellar generations. Conversely, we find no correlation between age and surface density (M/R_e^2 ) at 0.60 ≤ z ≤ 0.76, despite this relation being strong at low redshift. We consider this change in the age–M/R_e^2 relation in the context of the redshift evolution of the star-forming and quiescent mass–size relations, and find our results are consistent with galaxies forming more compactly at higher redshifts and remaining compact throughout their evolution. Furthermore, galaxies appear to quench at a characteristic surface density that decreases with decreasing redshift. The z ∼ 0 age–M/R_e^2 relation is therefore a result of building up the quiescent and star-forming populations with galaxies that formed at a range of redshifts and therefore a range of surface densities.